Buddhist thought : a complete introduction to the Indian tradition - Williams, Paul, 1950- (Routledge, 2012)
Buddhist Thought is crucial reading for those interested in Buddhism. It guides the reader towards a richer understanding of the central concepts of classical Indian Buddhist thought, from the time of Buddha to the latest scholarly perspectives and controversies. Abstract and complex ideas are made understandable by the authors' lucid style. The second edition has been thoroughly revised and updated throughout in light of new scholarship, in particular on Mahayana and tantric Buddhism. It now includes a section of further reading, study questions, a pronunciation guide and glossary of terms.